Adaptive Shrink and Shard Architecture Design for Blockchain Storage Efficiency - Daniel Soesanto; Igi Ardiyanto; Teguh Bharata Adji (IET Computers & Digital Techniques)
One of the problems in the blockchain is the formation of increasingly large data (big data) because each block must store all the transactions it makes. With the problem of the appearance of extensive data (big data), many studies aim to maintain the data in small amounts. This research combines a sorting data technique and a proper compression technique to obtain efficient data storage on the blockchain. The result of this research is a blockchain platform called Adaptive Shrink and Shard Blockchain (AS2BC), which conceptually and computationally can minimize the use of storage space in the blockchain up to 22 times smaller.